PENGARUH ELECTRONIC WORD OF MOUTH DAN KEMUDAHAN TRANSAKSI TERHADAP LOYALITAS PENGGUNA APLIKASI ACCESS BY KAI Survei Pada Pengguna Kereta Api Jarak Jauh Di Stasiun Bandung - Susi Oktavia Hidayah; Yoki Oktorian Sukardi (JURISMA : Jurnal Riset Bisnis & Manajemen, 2025)
The purpose of this study is to determine how much influence Electronic Word of Mouth and transaction ease have in increasing the loyalty of Access by KAI application users. The research method used is a descriptive verification method with a quantitative approach. The research instrument is measured using a Likert scale. The population in this study was accessed by KAI application users who ordered long-distance train tickets at Bandung Station. The sampling technique used was purposive sampling, with the number of respondents who met the research criteria. Data testing was carried out through validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, and hypothesis tests. The results of this study indicate that Electronic Word of Mouth partially has a significant effect on user loyalty of the Access application by KAI. Ease of transaction also has a significant partial effect on user loyalty. Simultaneously, both variables have a positive and significant effect on user loyalty of the Access application by KAI. This finding indicates that digital reviews and ease of transaction are important factors in building user loyalty towards application-based e-ticketing services. Keywords: EWOM; Ease of Transaction; User Loyalty; Transportation Sector; Management